2022
DOI: 10.1039/d1ob02317a
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium labelling to extract local stereochemical information by VCD spectroscopy in the C–D stretching region: a case study of sugars

Abstract: Stereochemical elucidation of molecules with multiple chiral centers is difficult. Even with VCD spectroscopy, excluding all but one diastereomeric structural candidates is challenging because stereochemical inversion of one chiral center...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…IR studies on nitriles have indicated anharmonic effects on their vibrational signals. 9 VCD signals of CRN stretching mode have been reported for (À)-trans-2-phenylcyclopropanecarbonitrile ( 17), (+)-trans-1,2-cyclopropanedicarbonitrile (18), and (R)-2-chloropropionitrile (19). 12a,26 These simple molecules showed a monosignate CRN stretching VCD signal without severe anharmonic perturbation.…”
Section: Nitrilementioning
confidence: 99%
See 2 more Smart Citations
“…IR studies on nitriles have indicated anharmonic effects on their vibrational signals. 9 VCD signals of CRN stretching mode have been reported for (À)-trans-2-phenylcyclopropanecarbonitrile ( 17), (+)-trans-1,2-cyclopropanedicarbonitrile (18), and (R)-2-chloropropionitrile (19). 12a,26 These simple molecules showed a monosignate CRN stretching VCD signal without severe anharmonic perturbation.…”
Section: Nitrilementioning
confidence: 99%
“…17 Isotopologues of bigger (bio)molecules have not been reported except for a small set of deuterated mono- and disaccharides (Fig. 3) 18 despite the establishment of efficient reactions to prepare various deuterated molecules. 19 VCD studies of deuterated bioactive molecules should gain more importance with the increasing trend in the development of deuterated medicines: deutetrabenazine and deucravacitinib are approved by FDA and several deuterated drug candidates are under clinical studies.…”
Section: C–d Chromophoresmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Recently, we have also found that VCD signals originating from OCD 3 vibrations in the 2300-1900 cm −1 region reflect the AC of an asymmetric center in the vicinity of the OCD 3 group with little influence from other chiral centers. 11 Because no previous VCD studies dealt with allenic molecules containing more than one chiral center, influence from other chiral centers to the VCD signal of ν as CvCvC is not known. Here, through VCD studies on allenic natural products and several synthetic model allenes, we discuss the scope and limitations of the use of a ν as CvCvC VCD signal for the AC determination of allenes.…”
Section: Introductionmentioning
confidence: 99%
“…42 Non-covalent derivatization methods to simplify calculations of carboxylic acids have been recently devised, 43 along with the covalent introduction of a suitable deuterated VCD chromophore with absorption removed from the IR fingerprint region for the C-1 configuration of sugar molecules. 44 Our group has been particularly interested in finding IR/VCD spectral signatures for conformation and configuration of chiral natural products. Examples include VCD markers for the configuration of esterified chromane and monoterpene moieties, 45 for the configuration of the hexahydroxydiphenoyl (HHDP) group in ellagitannins, 46 for the configuration of the 2(5 H )-furanone moiety in acetogenins, 47 for the configuration at C-9 of both strepchazolin A and B, 48 as well as the IR marker for the E / Z double bond configuration of spongosoritins 49 and the VCD marker for the stacking of the pyrrolidine ring of proline and the aromatic ring of tyrosine in pohlianin A.…”
Section: Introductionmentioning
confidence: 99%